Rotary Parking Design Using DC Motors with RFID and IoT-Based Monitoring (Internet of Things) via Telegram - Nurhaida; Susanti, Indah (International Journal of Research in Vocational Studies (IJRVOCAS), 2025)
Parking in dense urban areas is a big challenge because the increase in the number of vehicles causes a shortage of parking spaces, congestion and air pollution. As the number of vehicles increases, parking space is needed to accommodate many vehicles. Limited land often results in illegal parking which has a negative impact resulting in traffic jams. Rotary parking is one solution to maximize the use of limited parking space more efficiently. To move rotary parking, a DC motor is needed. In this rotary parking design, which has a capacity of 20 kg, a DC shunt wiper motor with a power capacity of 10-50 watts, 12VDC, and a current of 1-4 Ampere was chosen. This system is equipped with RFID technology to ensure safe vehicle access. The test was carried out eight times with gradual loads ranging from 16.5 kg to 20 kg. The results show that the tool can work well at each stage, with output power ranging from 14.46 watts at a load of 16.5 kg to 12.76 watts at a load of 20 kg. In conclusion, this rotary parking system can work as expected, efficiently handling the carload and a total load of 20 kg, as well as providing additional security using RFID and easy monitoring via IoT.